5(2c-1)-3=5c+7

Simple and best practice solution for 5(2c-1)-3=5c+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2c-1)-3=5c+7 equation:


Simplifying
5(2c + -1) + -3 = 5c + 7

Reorder the terms:
5(-1 + 2c) + -3 = 5c + 7
(-1 * 5 + 2c * 5) + -3 = 5c + 7
(-5 + 10c) + -3 = 5c + 7

Reorder the terms:
-5 + -3 + 10c = 5c + 7

Combine like terms: -5 + -3 = -8
-8 + 10c = 5c + 7

Reorder the terms:
-8 + 10c = 7 + 5c

Solving
-8 + 10c = 7 + 5c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5c' to each side of the equation.
-8 + 10c + -5c = 7 + 5c + -5c

Combine like terms: 10c + -5c = 5c
-8 + 5c = 7 + 5c + -5c

Combine like terms: 5c + -5c = 0
-8 + 5c = 7 + 0
-8 + 5c = 7

Add '8' to each side of the equation.
-8 + 8 + 5c = 7 + 8

Combine like terms: -8 + 8 = 0
0 + 5c = 7 + 8
5c = 7 + 8

Combine like terms: 7 + 8 = 15
5c = 15

Divide each side by '5'.
c = 3

Simplifying
c = 3

See similar equations:

| 6x+2+40=90 | | 3(2x-15)-4=55 | | 7y=27 | | 2t-6=3(t+6) | | -3x+12=-12 | | 5x+34=73 | | 90.50-77.75= | | 7x+8-2x=18 | | .7x+1=-3 | | 3(2x-15)=55 | | 21+x=25+2x | | 35x-3=214 | | 30-18=4(x-1) | | g=0.16(w+40) | | 30+275=1225 | | -4x-8=32 | | 5-.75x=-7 | | 10a-2=7a+1 | | 1x+-8=3(-2x+9) | | 50c-300=250 | | z^2-6X+7=2 | | 3x+24=63 | | 8k^4*2k= | | x^2-12=3 | | 2/3-7/4=5/12 | | -[x-(6x+7)]=7-(9x+3) | | 6-1b=5b+30 | | 5x+2=469 | | 4x-6=-90 | | c=2(4/2) | | 5=1halfm+3 | | -5(z+2)+4z= |

Equations solver categories